Effect of Ferredoxin Receptor FusA on the Virulence Mechanism of Pseudomonas plecoglossicida - He, Rongchao; Wang, Jiajia; Lin, Miaozhen; Tian, Jing; Wu, Bi; Tan, Xiaohan; Zhou, Jianchuan; Zhang, Jiachen; Yan, Qingpi; Huang, Lixing (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudomonas plecoglossicida is an aerobic Gram-negative bacterium, which is the pathogen of "Visceral white spot disease" in large yellow croaker. P. plecoglossicida is a temperature-dependent bacterial pathogen in fish, which not only reduces the yield of large yellow croaker, but also causes continuous transmission of the disease, seriously endangering the healthy development of fisheries. In this study, a mutant strain of fusA was constructed using homologous recombination technology. The results showed that knocked-out of P. plecoglossicida fusA significantly affected the ability of growth, adhesion, as well as the biofilm formation. Temperature, pH, H2O2, heavy metals and the iron-chelating agent were used to treat wild-type of P. plecoglosscida , the results showed that the expression of fusA was significantly reduced at 4℃, 12℃ and 37℃; the expression of fusA was significantly increased at pH 4 and 5; Cu2+ has a significant inducing effect on the expression of fusA, but Pb2+ has no obvious effect; the expression of fusA was significantly up-regulated under different concentrations of H2O2, the expression of fusA gene was significantly up-regulated in the 0.5~4 μmol/L iron-chelating agent. The expression level of fusA gene was significantly up-regulated after the logarithmic phase. It was suggested that fusA included in the TBDRs family was not only involved in the transport of ferredoxin, but also played important roles in the pathogenicity and environment adaptation of P. plecoglossicida.